Across the pond: An exploration of the American collegiate system as a pathway for elite British female gymnasts - Franklin, G. H.; Brown, D: J.; Vickers, E.; Harrison, G. E. (The Sport Psychologist, 2023)
The number of elite athletes from the United Kingdom choosing to migrate to the United States is increasing. Grounded in the push-pull framework, this was the first study to exclusively explore the motivations and experiences of elite British female gymnasts who migrated to American universities and competed in the National Collegiate Athletic Association. Data were collected using semistructured interviews with seven former gymnasts and analyzed using thematic analysis. The results document how this pathway provided gymnasts with an opportunity to extend their career in a positive environment, escaping the intense and autocratic culture that dominated gymnastics in Britain. Moreover, this pathway facilitated lasting athletic and personal development including enhanced retirement from the sport. From a practice standpoint, it appears important that gymnasts be educated about the pathways available to them and that British sport organizations be supported in reshaping their environments to create more desirable and sustainable systems.